2011
DOI: 10.3168/jds.2010-3979
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with nonconventional feeds from the Middle East: Assessing the effects on physicochemical and organoleptic properties of Awassi sheep milk and yogurt

Abstract: Increased feed costs affect the livelihoods of dairy sheep farmers in the Middle East. Farmers endure high risks with large fluctuations in the price of grain used as animal feed, which is further affected by drought and declining range productivity. Using agricultural by-products and treated straw or vetch grazing for supplementing sheep diets would provide resource-poor dairy farmers with increased options to reduce feed costs, but the effects of such feeds on the quality of yogurt (the main product) need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
7
1
2
Order By: Relevance
“…It is reported that starter culture had a meaningful impact on gumminess and chewiness of yogurt (Penna et al., 2006). Adhesiveness is strongly linked to firmness (Hilali et al., 2011). Mani‐López et al.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that starter culture had a meaningful impact on gumminess and chewiness of yogurt (Penna et al., 2006). Adhesiveness is strongly linked to firmness (Hilali et al., 2011). Mani‐López et al.…”
Section: Resultsmentioning
confidence: 99%
“…Pode-se verificar que o produto apresentou 83,77 % de umidade e 0,24 % de cinzas, corroborando com os dados obtidos por Mishra e Kumar (2004), que encontraram 81,9 % de umidade e 0,7 % de cinzas no iogurte de leite de ovelha. O teor de lactose foi de 4,59 %, estando próximo aos valores encontrados por Katsiari et al (2001) e Hilali et al (2011), que foram de 4,87 % e 4,84 %, respectivamente, no iogurte de leite de ovelha.…”
Section: Resultados E Discussõesunclassified
“…O resultado de acidez encontrado está de acordo com o padrão estabelecido pela IN nº 46, do regulamento técnico de identidade e qualidade de leites fermentados (Brasil, 2007), que é de 0,6 a 2 g/100g. O valor de acidez obtido neste trabalho foi similar aos encontrados por Pinto et al (2012) e Hilali et al (2011), que foram de 1,2g/100g e 1,52g/ 100g, respectivamente, ao final da fermentação em iogurte de leite de ovelha.…”
Section: Características Físico-químicas Do Iogurte De Leite De Ovelhaunclassified